PENCEGAHAN STUNTING MELALUI EDUKASI JAM’IYAH AISYIYAH KUDUS - Sukarmin Sukarmin; Diah Andriani; M. Fauzi Bahari; Hendra S. Kurnia; Ulin Nuha; Muhammad Abdul Rozaq (Universitas Muhammadiyah Kudus, 2023)
AbstractStunting is still a major problem in developing countries, including Indonesia. Stunting will have an impact on brain development and children's thinking skills and trigger various serious diseases. Education is one of the efforts that can be done in reducing the incidence of stunting. Education can play a role in increasing understanding and application of stunting prevention. The education conducted on 35 people of Jam'iyah Aisyiyah Kudus used lecture and discussion techniques as well as evaluation instruments consisting of 10 questionnaires on stunting conducted before and after education. The evaluation results after education showed 42.8% of the majority of of knowledge was high. These results show the importance of education about stunting needs to be encouraged at community meetings. Keywords: education, application, stunting reduction, knowledge